Application of Information Technologies in the Field of Physical Culture and Sports Tourism - DRAGICH, Olga A.; KLYUSHNIKOVA, Elena A.; SIDOROVA, Klavdiya A.; CHEREMENINA, Natalia A.; TATARNIKOVA, Natalia A. (Journal of Environmental Management and Tourism; Vol 9 No 8 (2018): JEMT Volume IX Issue 8(32) Winter 2018, 2019)
The necessity of using computer programs and other information technology tools for solving methodological problems for those engaged in physical culture is grounded in the paper. Along with training exercises, it is necessary to introduce a theoretical section that shapes the world outlook system of scientific and practical knowledge and attitude to physical culture. The authors propose to introduce courses, used for independent mastering the theoretical and methodical sections of the discipline “Physical Culture”. The introduction of E-learning support means will contribute to improving the level of educational, methodological and scientific work of the subject-cycle commission for physical culture, sports.